When lions roar the Churchills and the Kennedys - Maier, Thomas 1956- (Crown, 2014)
A far-reaching history of the intertwined personal and public lives of the Churchills and the Kennedys discusses their respective family views, how they overcame bitter differences to unite against Hitler and the enduring influence of their collaborations
Includes bibliographical references(pages 725-749) and index
Dynasty and Empire -- Family Fortunes -- Wartime -- Making Peace --
Keywords: Churchill, Winston / 1874-1965 / Friends and associates; Kennedy, John F. / (John Fitzgerald) / 1917-1963 / Friends and associates; Churchill, Winston / 1874-1965 / Family; Kennedy, John F. / (John Fitzgerald) / 1917-1963 / Family; Churchill family; Kennedy family; Churchill, Winston -- 1874-1965; Churchill -- Familie; Kennedy, John F. -- 1917-1963; Kennedy -- Familie; Geschichte 1900-2000; Politik; Great Britain / Relations / United States; United States / Relations / Great Britain; Great Britain / Politics and government / 20th century; United States / Politics and government / 20th century; Großbritannien; USA